The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0333102420944872
|View full text |Cite
|
Sign up to set email alerts
|

Proposed modified diagnostic criteria for recurrent painful ophthalmoplegic neuropathy: Five case reports and literature review

Abstract: Background Recurrent painful ophthalmoplegic neuropathy (RPON) is an uncommon disorder characterized by recurrent unilateral headache attacks associated with ipsilateral ophthalmoplegia. We intend to study the clinical picture in our case series along with the published literature to discuss the pathogenesis and propose modified diagnostic criteria for recurrent painful ophthalmoplegic neuropathy. Methods We reported five cases diagnosed as ophthalmoplegic migraine/RPON in our medical centers and reviewed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(69 citation statements)
references
References 65 publications
(119 reference statements)
1
64
0
4
Order By: Relevance
“…Although two attacks are necessary, it strongly suggests to consider RPON even at the rst attack, in presence of described characteristics. Thus, as mentioned by Wong(11) and Yinglu (14), we suggest to add into the diagnostic criteria the MRI ndings, including enhancement and thickening of the nerve involved. We analyzed the relationship between RPON and schwannoma.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although two attacks are necessary, it strongly suggests to consider RPON even at the rst attack, in presence of described characteristics. Thus, as mentioned by Wong(11) and Yinglu (14), we suggest to add into the diagnostic criteria the MRI ndings, including enhancement and thickening of the nerve involved. We analyzed the relationship between RPON and schwannoma.…”
Section: Discussionmentioning
confidence: 88%
“…In cases where MRI was negative, it is important to understand whether the imaging was really negative or the timing was wrong. In fact, in some patients there is no evidence of MRI abnormalities neither during the interictal phase nor during the rst attack and it could only be found after attacks (14). Therapy in acute phase had been administered in 70% of patients using corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Oculomotor nerve enhancement has previously been confirmed to be an indication of a variety of underlying etiologies [6, 12-15], including Tolosa-Hunt syndrome, recurrent painful ophthalmoplegic neuropathy (RPON), and oculomotor nerve tumors, and our patients should be especially distinguished from these nonischemic causes. However, pain and ophthalmoplegia were not resolved within 72 h of starting corticosteroid therapy, and it had never been reported that the oculomotor nerve was solely thickened and enhanced without enlargement of the cavernous sinus in Tolosa-Hunt syndrome [13]. Several patients with RPON had also revealed unilateral thickening and enhancement of the oculomotor nerve, but the cisternal segment was almost always involved [13, 16].…”
Section: Discussionmentioning
confidence: 99%
“…However, pain and ophthalmoplegia were not resolved within 72 h of starting corticosteroid therapy, and it had never been reported that the oculomotor nerve was solely thickened and enhanced without enlargement of the cavernous sinus in Tolosa-Hunt syndrome [13]. Several patients with RPON had also revealed unilateral thickening and enhancement of the oculomotor nerve, but the cisternal segment was almost always involved [13, 16]. Solid tumors frequently demonstrate nodular enhancement of the cisternal segment of the oculomotor nerve, and some may show the extension of mass lesions into the cavernous sinus or even intraorbital extension through the superior orbital fissure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation